Accuracy of expert predictions of seizure freedom after epilepsy surgery. (August 2019) - Witt, Juri-Alexander; Krutenko, Tamara; Gädeke, Maria; Surges, Rainer; Elger, Christian E.; Helmstaedter, Christoph
Highlights: We evaluated the accuracy of expert predictions of postsurgical seizure freedom. The predicted and the actual seizure outcome were compared in 200 surgical cases. Predictions ranged from 30 to 90% (mean: 67%), the actual seizure freedom rate was 66%. Nine of 12 estimation categories showed a tolerable deviation of ≤10%. For the vast majority (83%) of patients a correct prediction was provided. Abstract: Purpose: To evaluate the accuracy of expert estimations of achieving seizure freedom after epilepsy surgery in the context of presurgical patient counseling. Method: The retrospective study comprised a random sample of 200 patients who underwent any type of resective epilepsy surgery at the University of Bonn Epilepsy Center and the routine 1-year postoperative control visit in the years from 2008–2016. The prediction by a team of epileptologists and the actual seizure outcome were extracted from the pre- and postsurgical medical files, respectively. A deviation of >10% was a priori defined as a relevant discrepancy. Results: Estimated chances of achieving seizure freedom ranged from 30 to 90% (mean: 67%). The actual seizure freedom rate was 66% (Engel Ia/ ILAE 1a). Nine of 12 estimation categories showed a tolerable deviation of ≤10%, none of these with a worse than expected outcome. Two estimation categories (40–50%, and 80%) showed a worse actual seizure outcome with deviations of −40% (n = 3); and −17% (n = 30), respectively. All in all, for 83% of the patients a correct prediction was provided. Conclusions: For the vast majority of surgical patients, the expert prediction of postsurgical seizure freedom at the 1-year follow-up was accurate despite the heterogeneity of patients and surgical procedures.